RETN rs3745368 polymorphism and resistin level in Javanese ethnic Indonesian obese: a case control study - Utami, Rizki Fajar; Hastuti, Pramudji; Sadewa, Ahmad Hamim (Jurnal Teknologi Laboratorium, 2019)
Obesity has become a global public health problem. It occurs due to a positive energy balance leading to adipose tissue expansion. White adipose tissue was an endocrine organ which secreted resistin. Resistin also produced by immune cells due to low chronic level inflammation might cause higher resistin level in obese people. Polymorphism +62G>A RETN gene was reported has a relationship with low resistin level and A allele as a protective allele. This study aimed to determine genotype and allele frequency distribution concerning resistin level. Another objective aimed to know the correlation between resistin level with body mass index. The design of the research was a case-control study with 122 people (18-40 y.o.), divided equally in the case group (BMI â‰¥ 27 kg/m2) and control group (BMI 18.5-24.9 kg/m2) without diabetes mellitus. Blood was taken after fasting a minimal 8 hours. Plasma was used to measure the resistin level. DNA genotyping was analyzed using PCR-RFLP. Genotyping result showed three genotypes of RETN gene +62G>A polymorphism (GG, GA, AA). There was no significant difference in genotype and allele frequency distribution related to obesity status (p=0.680; p=1) and resistin level (p=0.537) between case and control group. There was no significant difference in resistin level between case and control group (p=0.770). Resistin level was correlated with BMI in obese group (p= 0.05; r= -0.25). The present study concludes that there is no significant difference in genotype and allele frequency distribution related to obesity status and resistin level. Resistin level has a negative correlation with BMI.